Respuesta :
Answer:
x = {-3, 3}
Step-by-step explanation:
Simplifying
x2 + -9 = 0
Reorder the terms:
-9 + x2 = 0
Solving
-9 + x2 = 0
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '9' to each side of the equation.
-9 + 9 + x2 = 0 + 9
Combine like terms: -9 + 9 = 0
0 + x2 = 0 + 9
x2 = 0 + 9
Combine like terms: 0 + 9 = 9
x2 = 9
Simplifying
x2 = 9
Take the square root of each side:
x = {-3, 3}
Answer:
10^2=0
Step-by-step explanation
Because x by it self always means one it would technically be 1^2+9 which would equal 10^2=0